A case of acute lymphocytic gastritis related to treatment with pembrolizumab for metastatic urothelial carcinoma. Issue 2 (20th December 2022) - Fukiishi, Yousuke; Fukuhara, Hideo; Kurano, Yoshitaka; Shugimoto, Hiroki; Yamashita, Erika; Karasima, Takashi; Inoue, Keiji
Abstract : Introduction: Immune checkpoint inhibitors such as programmed cell death/−ligand 1 inhibitor and cytotoxic T‐lymphocyte‐associated antigen‐4 inhibitors have been widely used for various advanced malignancies. The mechanism of action for these inhibitors is the improvement of antitumor immunity via T‐cell modulation. On the contrary, immune‐related adverse events such as autoimmune colitis might arise in association with T‐cell activation. Upper gastrointestinal adverse events related to pembrolizumab have rarely been reported. Case presentation: A 72‐year‐old man underwent laparoscopic radical cystectomy for muscle‐invasive bladder cancer (pT2N0M0). Multiple lymph node metastases appeared in the paraaortic region. First‐line chemotherapy comprising gemcitabine and carboplatin failed to stop disease progression. After the administration of pembrolizumab as second‐line treatment, the patient showed symptomatic gastroesophageal reflux disease. Esophagogastroduodenoscopic biopsy of the gastric body showed severe lymphoplasmacytic and neutrophilic infiltration. Conclusion: We present acute gastritis related to pembrolizumab. Early eradication therapy may be able to control immune checkpoint inhibitor‐related gastritis.